Some aspects of socialist modernization in the Croatian cities - Bara, Mario (Array, 2020)
The paper focuses on the period of socialist modernization in Croatian urban settings, in a country guided by ideologically shaped administrative measures, absence of social pluralism, and private economic initiatives. The socialist regime mainly promoted the announced transformation of social and economic relations, as well as technical progress, in the urban areas, where cultural and symbolic interventions took place along with the technical ones. The socialist city was to become an ideal city that met all the needs of the “working people”. Industrialization and urbanization caused labour migration from rural to urban areas. Due to the large number of new residents in the cities, the authorities paid much attention to housing policies. Accelerated construction resulted in a discrepancy with the existing urban and communal infrastructure. The consequences of half a century of socialist modernization in the cities were most evident in the altered population structure. At the beginning of the observed period, only one quarter of the population lived in cities, but when the socialist epoch ended, this ratio was over 50 %. The negative consequences of socialist modernization in the cities could be seen in the polarized development of the main urban centres, the unevenly developed network of medium-sized and small towns, and the depopulation of a significant part of rural areas.